SOCIAL CHANGES IN THE CITY OF QARSHI - Qayumov Mirzokhid (Web of Journals Publishing, 2025)
This article analyzes the social development of the city of Qarshi during the years of independence.
Keywords: Theaters, cinemas, libraries, clubs, cultural palaces, industry, agriculture, education, healthcare, culture.